Examining the Mediating Role of Social Worth in the Effect of Employees’ Person Environment-Fit on Entrepreneurial Intention - MUMCU, ARTÜR YETVART (Beta Basım Yayım Dağıtım AŞ., 2025)
Purpose: To examine how employees’ person-environment fit influences their entrepreneurial intenti- ons and whether perceived social worth mediates this effect, in the context of Türkiye. Methodology: Survey data from 289 employees with at least five years’ work experience (251 valid responses) were analyzed using confirmatory factor analysis and structural equation modeling to test hypothesized relationships. Findings: Person-environment fit significantly increased entrepreneurial intention, particularly in the person-job fit dimension. Perceived social worth partially mediated this effect. Practical implications: Organizations can foster inclusive, supportive work environments to enhance employees’ social worth, strengthening entrepreneurial motivation and aiding talent retention and adaptability. Originality: The study provides a novel contribution to the literature by integrating person-environ- ment fit and social worth perspectives to explain entrepreneurial intention.
Çalışanların Çevre Uyumlarının Girişimcilik Niyetleri Üzerindeki Etkisinde Algıladıkları Sosyal Değerin Aracı Rolünün İncelenmesi
Keywords: Person Environment Fit; Social Worth; Entrepreneurial Intention